Kajian efisiensi penggunaan pupuk anorganik pada budidaya kacang panjang menuju pertanian berkelanjutan yang ramah lingkungan - Miftah Dieni Sukmasari; Aaz Azamudin Tifani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
The excessive use of inorganic fertilizers in the cultivation of long beans (Vigna unguiculata subsp. sesquipedalis) has a negative impact on the sustainability of soil ecosystems. This study aims to examine the efficiency of the use of NPK fertilizer combined with mycorrhizal and Rhizobium biological fertilizers in long bean plants. The experiments were arranged in a Randomized Group Design (RAK) with five treatments: control without fertilizer, single NPK (100% recommended dose), NPK+Mycorrhizae+Rhizobium (100% NPK), and single Rhizobium and single Mycorrhizae, each repeated four times. The parameters observed included vegetative growth, root system, nitrogen uptake, crop components, and nitrogen use efficiency (NUE). The results showed that single Rhizobium inoculation resulted in the highest pod weight (101.3 g/plant), the highest seed weight (70.9 g/plant), and the highest nitrogen uptake (2.05 g/plant), outperforming the full NPK treatment. The combination of NPK+Mycorrhizae+Rhizobium provides the highest NUE value and the best root system with a root length of 43.3 cm and a number of nodules of 52.2. Rhizobium inoculation has proven to have the potential to be an efficient and environmentally friendly substitution of inorganic nitrogen fertilizer in long bean cultivation.